IMPLEMENTASI PEMBELAJARAN PAI BAGI ANAK BERKEBUTUHAN KHUSUS TUNAGRAHITA DI SLBC NEGERI PEMBINA PROVINSI KALIMANTAN SELATAN - Puteri Aisyah; Miftahul Jannah (Program Studi PAI STAI Al Falah Banjarbaru, 2026)
Every child has the right to receive an education to develop their potential, including children with disabilities. For example, children with special needs and intellectual disabilities are individuals with intellectual and cognitive abilities that are below average compared to the general population. Although they suffer from mental retardation and slow physical development, this does not mean they are incapable of doing anything. Their skills can still be trained and developed, and they can even achieve success. Against this background, this study discusses the implementation of Islamic Religious Education (PAI) learning for children with special needs and intellectual disabilities at SLB C Negeri Pembina, South Kalimantan Province. The formulation of the research problem is how to implement Islamic Religious Education learning for children with special needs and mental retardation at SLB C Negeri Pembina, South Kalimantan Province, and what factors support and hinder this process. The subjects of this study were Islamic Religious Education (PAI) teachers. The object of this study was the implementation of Islamic Religious Education (PAI) learning for students with special needs and intellectual disabilities at SLB C Negeri Pembina, South Kalimantan Province, and its supporting and inhibiting factors. Data collection techniques used in this study were interviews, observation, and documentation. Data processing was carried out using data reduction, presentation, and verification techniques. Meanwhile, data analysis used triangulation analysis. The results of this study indicate that the implementation of Islamic Religious Education (PAI) learning for children with special needs and intellectual disabilities at SLB C Negeri Pembina, South Kalimantan Province, has been planned through the development of lesson plans (RPP)/teaching modules, preparation of teaching materials, and selection of methods and media to be used. There are no significant differences in the teaching methods used by Islamic Religious Education (PAI) teachers for children with intellectual disabilities compared to those of normal students. The teaching methods are still adapted to the students' needs, and teachers need patience in repeating the material presented to ensure comprehension and understanding. Evaluations still include PTS (Private Exam) and UAS (Final Exam) assessments, which include cognitive, psychomotor, and affective assessments, similar to those conducted in general schools. Factors supporting and hindering the implementation of Islamic Religious Education (PAI) learning for children with special needs and intellectual disabilities include teachers, infrastructure, and parents. Through optimal teaching effort, adequate supporting infrastructure and the full involvement of parent, student can archieve their maximum potential.